Does intellectual capital add value to Malaysian companies? - Kamardin, Hasnah; Abu Bakar, Robiah; Ishak, Rokiah; Ku Ismail, Ku Nor Izah; Mohd Yusof, 'Atef (2013)
In knowledge-based economy, intellectual capital (IC) plays an important role compared to the physical assets in achieving a company value and success.The ignorance of IC would result in management putting less attention on IC, and hence IC value added capabilities would not be fully exploited.The study aims to examine the relationship between IC performance (VAIC) and company characteristics with IC disclosure in the annual reports of 68 biggest Malaysian companies listed in Bursa Malaysia based on market capitalization in year 2006.The study follows the classification of IC disclosure (ICD) by Huang et al. (2007), with three broad IC categories in forty-five items. Content analysis was used to collect the IC related information.Other data are gathered from annual reports and datastream.Results show that VAIC is negatively related to IC disclosure.Further classification of VAIC shows that Intellectual Capital Efficiency (ICE) and Human Capital Efficiency (HSE) are negatively related to IC disclosure whilst Structural Capital Efficiency (SCE) is not related to IC disclosure.Negative association suggests that companies reduce intellectual capital disclosure for competitive advantage reason which supports the proprietary cost theory.Company size and leverage are found to be positively related to IC disclosure.